(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
This paper aims to analyze the measurement equivalence aspects (internal consistency and interrater reliability) of a Brazilian version of Martín-Bayarre-Grau (MBG) adherence questionnaire as part of its cross-cultural adaptation. Item-total correlation and Cronbach's alpha coefficients were used as internal consistency estimates. Stability was evaluated through test and retest comparison and expressed through intraclass correlation coefficient (ICC) and kappa with quadratic weighting. ICC for the overall scale was 0.81, indicating an "almost perfect" agreement. However, some cases of "poor" and "slight" agreements were found while analyzing individual items. The translated version of the MBG questionnaire showed good homogeneity (alpha 0.78), higher than cutoff points suggested in the literature. The scale has proved capable of measuring the level of adherence to treatment in hypertensive and/or diabetic patients in a reliable way.